2007
DOI: 10.1523/jneurosci.3216-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Regulation of Pair Bond Formation by cAMP Signaling within the Nucleus Accumbens Shell

Abstract: The formation of monogamous pair bonds, by prairie voles, is facilitated by activation of dopamine (DA) D 2 -like, but not D 1 -like, receptors within the nucleus accumbens (NAcc) shell. Because DA exerts opposing regulation of cAMP production depending on the subtype of receptor activated, we tested the hypothesis that DA regulation of pair bond formation is mediated via the cAMP signaling cascade. Consistent with activation of D 2 -like receptors, decreasing cAMP signaling, by blocking cAMP binding sites on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 52 publications
3
34
0
Order By: Relevance
“…Here, we demonstrate that blockade of -opioid receptors (known to mediate aversion) (Mucha and Herz, 1985;Pfeiffer et al, 1986), but not -opioid receptors (known to mediate reward and positive hedonics) (Weeks, 1962;Bozarth and Wise, 1981), prevents selective aggression. These effects are specific to the NAc shell, a component of brain motivational circuitry that is critical for neural processing of both social bonding (Li and Fleming, 2003;Champagne et al, 2004;Aragona et al, 2006;Aragona and Wang, 2007) and unconditioned incentives, including those of an aversive nature (Kalivas and Duffy, 1995;Ikemoto and Panksepp, 1999;Kelley and Berridge, 2002;Everitt and Robbins, 2005;Becker, 2009). As such, the current data suggest that -opioid receptors within this region may facilitate the tagging of social stimuli as aversive and cause novel conspecifics to be aggressively rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate that blockade of -opioid receptors (known to mediate aversion) (Mucha and Herz, 1985;Pfeiffer et al, 1986), but not -opioid receptors (known to mediate reward and positive hedonics) (Weeks, 1962;Bozarth and Wise, 1981), prevents selective aggression. These effects are specific to the NAc shell, a component of brain motivational circuitry that is critical for neural processing of both social bonding (Li and Fleming, 2003;Champagne et al, 2004;Aragona et al, 2006;Aragona and Wang, 2007) and unconditioned incentives, including those of an aversive nature (Kalivas and Duffy, 1995;Ikemoto and Panksepp, 1999;Kelley and Berridge, 2002;Everitt and Robbins, 2005;Becker, 2009). As such, the current data suggest that -opioid receptors within this region may facilitate the tagging of social stimuli as aversive and cause novel conspecifics to be aggressively rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Although such electrophysiological studies are unable to identify the subtype of DA receptors expressed on individual neurons, anatomical studies demonstrate that the NAcc is comprised of projection neurons that express either D1Rs or D2Rs with very little coexpression (33). Psychostimulants preferentially activate intracellular signaling pathways downstream from D1Rs (as determined by increased phosphorylation of signaling molecules) (34) and we have previously shown that increased activation of these signaling pathways prevents partner preference formation (35). Thus, although DA transmission within the NAcc plays an important role in the response to AMPH and the formation of partner preferences, these behaviors are likely mediated through distinct microcircuitries that comprise striatal projection systems (33,36).…”
Section: Discussionmentioning
confidence: 99%
“…Specific antisense riboprobes (Table 1) were used for D1R, D2R, TH, and DAT in situ mRNA labeling. Labeling was conducted with 35 S-labeled probes and sense mRNA controls for each DA marker as previously described (51). For Western blotting analysis, DAR protein was extracted from the supernatant of NAcc tissue punches and assayed as described previously (52).…”
Section: Methodsmentioning
confidence: 99%
“…Data from prairie voles has provided strong evidence that the dopaminergic system, specifically dopamine (DA) in the nucleus accumbens (NAcc), plays a fundamental role in the formation and maintenance of pair-bonds [Aragona et al 2003; Aragona et al 2006; Aragona and Wang 2007; Curtis et al 2006; Gingrich et al 2000; Liu et al 2010; Liu et al 2011; Young et al 2011a; Young et al 2011b]. The NAcc is a key neuroanatomical structure involved in various rewarding behaviors.…”
Section: Introductionmentioning
confidence: 99%